2017
DOI: 10.1007/s11999-016-4794-3
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Level of Nerve Root Resection in En Bloc Sacrectomy Influence Patient-Reported Outcomes?

Abstract: Background For patients with sacral tumors, who are well enough for surgery, en bloc resection is the preferred treatment. Survival, postoperative complications, and recurrent rates have been described, but patient-reported outcomes often are not included in these studies. Questions/purposes The purposes of this study were (1) to compare patient-reported outcomes after en bloc sacrectomy, based on the level of sacral nerve root resection, in terms of mental health, physical health, bowel function, and sexual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…In the present cases, the S 3 nerve roots and above were preserved and no patients had experienced local recurrence during the follow up. The neurologic outcome of the present study is in accordance with the results reported in the literature [14][15][16]18,19 . Larger studies are encouraged to ascertain the efficacy of variable management approaches.…”
Section: Discussionsupporting
confidence: 92%
“…In the present cases, the S 3 nerve roots and above were preserved and no patients had experienced local recurrence during the follow up. The neurologic outcome of the present study is in accordance with the results reported in the literature [14][15][16]18,19 . Larger studies are encouraged to ascertain the efficacy of variable management approaches.…”
Section: Discussionsupporting
confidence: 92%
“…[27][28][29] The use of the calculator in sarcoma patients, however, has been limited; with a study by Slump et al 23 showing it was a poor predictor of complications following flap reconstruction for extremity sarcoma. One likely reason for this is that tumor-related factors such as the size and the location (high vs low sacrectomy), which have been shown to influence the outcome in chordoma, 2,15,30 are not accounted for based on the CPT codes available and not captured by the calculator.…”
Section: Methodsmentioning
confidence: 99%
“…All patients had bowel and bladder dysfunction postoperatively . van Wulfften Palthe et al reported 10 patients who received en bloc sacrectomy with the L5 nerve root spared. They investigated the postoperative outcomes using the National Institutes of Health Patient Reported Measurement Information System and concluded that a preoperative discussion should occur with these patients about the potential effects on physical and mental functions .…”
Section: Discussionmentioning
confidence: 99%
“…van Wulfften Palthe et al reported 10 patients who received en bloc sacrectomy with the L5 nerve root spared. They investigated the postoperative outcomes using the National Institutes of Health Patient Reported Measurement Information System and concluded that a preoperative discussion should occur with these patients about the potential effects on physical and mental functions . After a thorough literature review, we believe the sample size of the current study is the largest to date, which might allow us to evaluate the oncological prognosis of total en bloc sacrectomy and the effect of this procedure on patient experiences.…”
Section: Discussionmentioning
confidence: 99%